"You're a Trickster": Mockery, Egalitarianism, and Uncertainty in Northeastern Namibia. Issue 1 (1st March 2019) - Laws, Megan
Abstract : The trickster has held a prominent place in the study of folklore, as much as it has been central to anthropological understandings of egalitarianism. In both, the trickster embodies an insoluble tension between the repressed, amoral desires of the individual and the moral demands of social life. This tension, so it goes, is visible in the ambiguity of the figure—a protean indeterminate being, neither good nor bad. Among the Jú|'hoànsi of northeastern Namibia, the trickster is similarly ambiguous. The figure conveys not a clash of values, but rather the doubt and uncertainty people feel toward those with whom they share resources, or about different ways of sharing and how they might relate to one another. This article approaches such uncertainty through a focus on the mocking phrase "you're a trickster" and the moral discourses that accompany it.